UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL TGT (TEAMS GAMES TOURNAMENT) PADA MATA PELAJARAN MATEMATIKAKELAS IV DI SDN DINOYO - Max Faisal Bahreizy; Agung Setyawan (CV. ADIBA AISHA AMIRA, 2023)
This research was conducted because there were problems that occurred at SDN Dinoyo Lamongan. The problem is the low learning outcomes of fourth grade elementary school students. The formulation of the problem in this study is how to improve students' cognitive learning outcomes through the TGT learning model. The purpose of this research is to improve students' cognitive learning outcomes through the TGT learning model. This type of research includes classroom action research. Techniques and methods used to collect data in a quantitative way through learning outcomes in the form of evaluation scores at the end of learning. In addition, observations and interviews were also carried out with class IV teachers. The results of this study showed an increase of 58% in cycle I and 70% in cycle II. The TGT model has a positive influence on student learning outcomes seen from the increase in cycles I and II. The increase in the number of students who were able to complete learning also increased by 5 students. cycle I the number of students completing as many as 14 students increased by 5 students completing to 19 students completing.